PEMBELAJARAN IPA BERBASIS ETHNO-STEM BERBANTU MIKROSKOP DIGITAL UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DI SEKOLAH PERBATASAN - Niken Eka Priyani; Nawawi Nawawi (PGSD Universitas Muria Kudus, 2020)
The purpose of the study was to obtain an overview of the application of Science Learning Based on Ethno-STEM with Digital Microscope, and to find out how the application of Science Learning Based on Ethno-STEM in improving the Science Process Skills of fourth grade students at SD Negeri 29 Idai. The type of research used is classroom action research (PTK) which consists of four stages in each cycle, namely planning, implementing, observing, and reflecting. The research was conducted in two cycles, each of which consisted of one meeting. The research data collection tools were the observation sheet of science process skills and student worksheets. The data analysis technique used qualitative and quantitative analysis techniques. The results of the assessment of Science Process Skills showed that there was an increase in the ability to observe students from 45.83% to 64.58%, the ability to classify students from 39.58% to 54.17%, the ability to predict students from 43.75% to 56, 25%, the ability to submit hypotheses from 39.58% to 54.17%, the ability to conclude 39.58% to 56.33%, and application skills from 31.25% to 58.33%. So it can be concluded that Ethno-STEM learning assisted by a simple digital microscope can improve the Science Process Skills of SDN 29 Idai students.